2019
DOI: 10.1002/14651858.cd010277.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Chest physiotherapy for pneumonia in children

Abstract: Analysis 1.2. Comparison 1 Chest physiotherapy compared with no chest physiotherapy, Outcome 2 Duration of hospital stay..... Analysis 1.3. Comparison 1 Chest physiotherapy compared with no chest physiotherapy, Outcome 3 Time to clinical resolution (respiratory rate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 72 publications
1
20
0
10
Order By: Relevance
“…Also, the study results illustrated that mean scores of body temperature, respiratory rate, heart rate and oxygen saturation among infants with pneumonia was not changed on admission day in each group but improved in the intervention group at 1st, 2nd, 3rd and 4th days post the regular chest percussion while not improved in the control group. The present result goes on same line with Chaves et al [21] who reported a positive improvement in respiratory rate and oxygen saturation after chest physiotherapy. A study done by Lestari et al [22] showed a difference between the two groups in heart rate, respiratory rate, and oxygen saturation means score.…”
Section: Discussionsupporting
confidence: 93%
“…Also, the study results illustrated that mean scores of body temperature, respiratory rate, heart rate and oxygen saturation among infants with pneumonia was not changed on admission day in each group but improved in the intervention group at 1st, 2nd, 3rd and 4th days post the regular chest percussion while not improved in the control group. The present result goes on same line with Chaves et al [21] who reported a positive improvement in respiratory rate and oxygen saturation after chest physiotherapy. A study done by Lestari et al [22] showed a difference between the two groups in heart rate, respiratory rate, and oxygen saturation means score.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, many physiotherapy services have preventive effects, which can put a stop to expensive interventions such as surgeries in future [20,22,48]. Additionally, some physiotherapy interventions if prescribed until the age of 18 years, can be very effective [49,50]. In this regard, the Netherlands has included physiotherapy services needed by children up to the age of 18 years in its basic health bene t package [11].…”
Section: Bene T Packagementioning
confidence: 99%
“…In fact, many physiotherapy services have preventive effects, which can prevent expensive interventions such as surgery in future [17,19,41]. Additionally, some physiotherapy interventions if prescribed until the age of eighteen, can be very effective [42,43]. Therefore, considering these interventions and also cost-effectiveness strategies can be included in benefit packages [44].…”
Section: Benefit Packagementioning
confidence: 99%